2018
DOI: 10.1002/ddr.21485
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, optimization, and pharmacokinetic study of nanoliposomes loaded with triacylglycerol‐bound punicic acid for increased antihepatotoxic activity

Abstract: Punicic acid of pomegranate oil (PAP) has gained heightened interest due to several health benefits, such as anticarcinogenic, antidiabetic, and antiatherosclerotic properties. However, these bioactivities have been hampered by chemical instability, poor water solubility, rapid metabolism, and low bioavailability of PAP. Therefore, this study was aimed at optimizing the liposomal formulation of Triacylglycerol‐bound punicic acid with its regioisomers (TPAR) for improved oral bioavailability and increased hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Natural products and its derived active constituents normally known as phytobioactive compounds have recently been explored in the treatment of several diseases [57][58][59][60]. In recent times, our exploits in phytocompounds research support the assertion that natural products have the potential to prevent and treat oxidative stress-related inflammation which underlie liver disorders [61,62].…”
Section: Prevention and Treatment Prospects Of Natural Phytobioactive Compoundsmentioning
confidence: 90%
“…Natural products and its derived active constituents normally known as phytobioactive compounds have recently been explored in the treatment of several diseases [57][58][59][60]. In recent times, our exploits in phytocompounds research support the assertion that natural products have the potential to prevent and treat oxidative stress-related inflammation which underlie liver disorders [61,62].…”
Section: Prevention and Treatment Prospects Of Natural Phytobioactive Compoundsmentioning
confidence: 90%
“…Several conditions and xenobiotics can disrupt the normal functioning of liver . Common xenobiotic used to mimic hepatotoxicity in animal models is carbon tetrachloride (CCl 4 ) which induces oxidative stress, lipid peroxidation and inflammation . Notably, CCl 4 induces injury via its metabolites (trichloromethyl) produced by cytochrome P450 systems .…”
Section: Introductionmentioning
confidence: 99%
“…Like other natural essential oils (EOs), the use of free cuminaldehyde usually leads to decreased bioactivity because of low bioavailability caused by volatilisation, hydrophobicity and rapid enzymatic metabolisation . Cuminaldehyde could therefore be formulated via appropriate novel techniques to enhance its oral bioavailability and therapeutic efficacy as other natural bioactive compounds . Several reports indicated that carriers such as liposomes, cyclodextrin inclusion complexes and drug‐in‐cyclodextrin‐in‐liposome systems have been used to encapsulate various EOs and their components, viz.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations